2021
DOI: 10.1186/s13068-021-01955-5
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of insoluble softwood substrates affect fungal morphology, secretome composition, and hydrolytic efficiency of enzymes produced by Trichoderma reesei

Abstract: Background On-site enzyme production using Trichoderma reesei can improve yields and lower the overall cost of lignocellulose saccharification by exploiting the fungal gene regulatory mechanism that enables it to continuously adapt enzyme secretion to the substrate used for cultivation. To harness this, the interrelation between substrate characteristics and fungal response must be understood. However, fungal morphology or gene expression studies often lack structural and chemical substrate cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 98 publications
1
8
0
Order By: Relevance
“…This is especially interesting considering the somewhat similar proportions of cellulose, hemicellulose, and lignin for the empty fruit bunch from oil palm ( 29 ), rice straw ( 30 ), sugar cane bagasse ( 31 ), and wheat straw ( 32 ). Differences in fungal secretomes have been demonstrated previously when grown on compositionally distinct carbon sources ( 33 35 ). However, the variation on broadly similar lignocellulosic substrates demonstrated here is important as it may suggest a tailoring of the lignocellulose-degrading enzymes produced by P. putredinis NO1 which could be utilized for substrate-specific cocktail development.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…This is especially interesting considering the somewhat similar proportions of cellulose, hemicellulose, and lignin for the empty fruit bunch from oil palm ( 29 ), rice straw ( 30 ), sugar cane bagasse ( 31 ), and wheat straw ( 32 ). Differences in fungal secretomes have been demonstrated previously when grown on compositionally distinct carbon sources ( 33 35 ). However, the variation on broadly similar lignocellulosic substrates demonstrated here is important as it may suggest a tailoring of the lignocellulose-degrading enzymes produced by P. putredinis NO1 which could be utilized for substrate-specific cocktail development.…”
Section: Resultsmentioning
confidence: 55%
“…The similarity in the proportion of GH class CAZymes in the supernatant fraction even for compositionally distinct substrates such as wheat bran and kraft lignin could be the result of the transcriptional activation of GH class CAZymes like cellulases and xylanases. Mono- and disaccharides, which could be present in all substrates investigated here, have been demonstrated to act as inducers of the expression of large numbers of hydrolytic CAZymes in other ascomycete fungi previously ( 35 , 51 ). This may be occurring for all substrates despite the target polysaccharides of induced enzymes not necessarily being present in similar amounts across all substrates investigated.…”
Section: Resultsmentioning
confidence: 60%
“…The enzymes were loaded based on activity measurements. The cellulolytic activity in Celluclast and Cellic CTec2 was determined using the filter paper unit (FPU) assay [ 50 ] with some adjustments [ 51 ]. The β-glucosidase activity of Novozym 188 was determined as described previously [ 52 ] with some adjustments [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fujii et al (2009) estimated the hydrolysis ability of the produced enzyme (Acremonium cellulolyticus) against woody biomass, Eucalyptus and Douglus fir, and conversion rates for both were above 69%, which was higher than the commercial enzyme (Accellase 1000), which was below 60%. Novy et al (2021) customized the enzyme mixture of Celluclast 1.5 L and cellulase from T. reesei and treated it with pretreated lodgepole pine, which represented approximately the same conversion rate as Cellic CTec 3 (80%). Aksenov et al (2020) observed that the conversion rate of bleached hardwood and softwood pulp with cellulase from Penicillium verruculosum and the reduced sugar yield were approximately 60%.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%